Efektivitas Sistem Informasi Perangkat Desa (Sipede) di Kecamatan Candi, Kabupaten Sidoarjo - Lailatul Fadiyah; Eva Hany Fanida; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (Perspektif Administrasi Publik dan hukum, 2026)
The use of information technology is a crucial element in improving the effectiveness of village government administration. One implementation of e-government at the village level is the use of the Village Apparatus Information System (Sipede) as a medium for managing village apparatus data. This study aims to analyze the effectiveness of Sipede's implementation in supporting village apparatus data management in Candi District. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and system document reviews. Data analysis was conducted using the Agile Response in E-Governance framework, which includes nine effectiveness indicators: Ease of Use, Usefulness, System Quality, Technology Mindfulness, Software Reliability, Communication Transparency, Trust, Collaboration Efficiency, and Traceability. The results show that Sipede is quite effective in improving data accuracy, information integration, and coordination between government agencies. This effectiveness is evident in the ease of use of the system, the clarity of the workflow, and the level of apparatus trust in the data generated. However, the use of Sipede still faces obstacles in the form of limited system access and suboptimal usage practices. Therefore, efforts are needed to develop systems and increase user capacity to support more accountable and sustainable village apparatus administrative governance.